Allergic shock caused by ingestion of cooked jellyfish: A case report. Issue 38 (September 2017) - Li, Zhixing; Tan, Xungang; Yu, Botao; Zhao, Renliang
Abstract: Rationale: Although anaphylaxis caused by jellyfish stings is common in coastal areas, an allergic shock caused by cooked jellyfish ingestion has never been reported in China. In this paper, we report a case of allergic shock being caused by ingestion of cooked salt-preserved jellyfish shortly after being stung by a live jellyfish. Patient concerns: A 26-year-old Chinese man presented with dizziness, pruritus, dyspnea, hypotension, and tachycardia after eating cooked salted jellyfish. The patient had been stung twice by jellyfish half a year ago. Diagnoses: Allergic shock caused by ingestion of cooked jellyfish. Interventions: The patient was treated with phenergan (25 mg, intramuscular injection), 250 mL normal saline (NS) and 10 mg dexamethasone (intravenous drip), 500 mL NS and 0.4 g cimetidine (intravenous drip), and 500 mL NS for rapid fluid infusion (intravenous drip). Outcomes: After the treatment, the main clinical symptoms of the patient improved quickly. Five days later, the patient's urticaria had dissipated. Lessons: A history of jellyfish contact or sting might be an important allergic factor for individuals who consume any kind of jellyfish.